School Strategic Planning Based on Appreciative Inquiry at Private High School in Lamongan City - Ahmad Farafis Hakkari; Cholichul Hadi; Muhammad Fahmi (Budapest International Research and Critics University, 2022)
This study aims to develop schools by designing and implementing a strategic planning based on appreciative inquiry at XYZ private high school in Lamongan. In practice, there are four aspects that are emphasized when doing strategic planning, including strengths, opportunities, aspirations, and results. Then, strategic planning activities based on appreciative inquiry led to concrete actions that were supported by all stakeholders. The methodology of this study uses an appreciative inquiry approach that has a cycle such as discovery, dream, design, and destiny with a mini workshop media on 24 employees of XYZ private high school while designing strategic planning. The measurement of the research success is measured by the process of holding a mini workshop, and the outcomes of the intervention provided. The results showed that the subject had a positive evaluation of the mini workshop activities and participated in the event with spirit and enthusiasm. Then, the outcomes of this study indicate that the subject experiences the impact of changes both individually and organizationally as well as the implementation of actions that have been designed. In short, the strategic planning carried out by school members has a positive impact and change in school development.